SiteWhat"s newContent pageFront pageIndex pageAboutPrivacy policySubjectsArithmeticAlgebraGeometryProbabilityTrigonometryArticlesCut the knot!What is what?Inventor"s paradoxMath as languageCollectionsOutline mathematicsBook reviewsInteractive activitiesDid you know?Eye openerAnalogue gadgets Proofs in mathematicsThings impossibleSimple mathFast Arithmetic TipsStories for youngWord problemsGames và puzzlesOur logoMake an identity Relations between various elements of a triangle

### 2S = ab sin(C)

This follows from 2S = aha because ha = b sin(C).

Bạn đang xem: Dựa vào công thức (1) và định lý sin, hãy chứng minh s = abc/4r

### S = rp

Triangle ABC is a union of three triangles ABI, BCI, CAI, with bases AB = c, BC = a, và AC = b, respectively. The altitudes lớn those bases all have the length of r.

### r² = p-1(p - a)(p - b)(p - c)

This follows from S² = p(p - a)(p - b)(p - c) và S = rp.

### 1/r = 1/ha + 1/hb + 1/hc

2S = aha = bhb = chc. Therefore, a = 2S/ha, etc. On the other hand, S = rp, so that p = S/r, or (a + b + c) = 2S/r. From here, 2S/ha + 2S/hb + 2S/hc = 2S/r.

### sin²(A/2) = (p - b)(p - c) / bc, etc.

First of all, sin(A) = 2·sin(A/2)cos(A/2) = 2·sin²(A/2)/tan(A/2). Therefore,

 (1) sin²(A/2) = sin(A)·tan(A/2) /2.

We know that

 (2) sin(A) = 2S / bc

and

 (3) tan(A/2) = r/(p - a).

Combining (1)-(3) gives

sin²(A/2) = 2S/bc · r/(p-a) · 1/2.

Taking into tài khoản that S² = p(p - a)(p - b)(p - c) & r² = p-1(p - a)(p - b)(p - c), the latter leads to

sin²(A/2) = (p - b)(p - c) / bc.

### cos²(A/2) = p(p - a) / bc, etc.

Indeed, from sin²(A/2) = (p - b)(p - c) / bc,

 cos²(A/2) = 1 - sin²(A/2) = 1 - (p - b)(p - c) / bc = (p(b + c) - p²) / bc = p((2p - a) - p) / bc = p(p - a) / bc.

### cos²<(C-B)/2> = <(b+c)²(p-b)(p-c)> /

This is the consequence of the previous two. Indeed, cos²<(C+B)/2>=sin²(A/2).

cos²<(C-B)/2>-cos²<(C+B)/2>=sin(C)sin(B)=4<ΔABC>²/(a²bc),

i.e.,

cos²<(C-B)/2>=sin²(A/2)+4p(p-a)(p-b)(p-c)/(a²bc).

In other words,

cos²<(C-B)/2>=(p-b)(p-c)/bc + 4p(p-a)(p-b)(p-c)/(a²bc)=(b+c)²(p-b)(p-c)/(a²bc).

### AI² = (p - a)bc/p

Square the obvious

AI = r/sin(A/2).

Substitute there sin²(A/2) = (p - b)(p - c) / bc and r² = p-1(p - a)(p - b)(p - c):
 AI² = p-1(p - a)(p - b)(p - c)bc/(p - b)(p - c) = (p - a)bc/p.

### bc·tan(B/2)·tan(C/2)

Squaring AI = r/sin(A/2) & substituting sin²(A/2) = (p - b)(p - c) / bc, we obtain

AI² = r²·bc/(p - b)(p - c).

By the incenter construction, tan(B/2) = r/(p - b) và also tan(C/2) = r/(p - c). Substituting these into the above gives the required

AI² = bc·tan(B/2)·tan(C/2).

### 1/r = 1/ra + 1/rb + 1/rc

As we know,

S = ra(p - a) = rb(p - b) = rc(p - c).

Therefore

 1/ra+ 1/rb + 1/rc = (p - a)/S + (p - b)/S + (p - c)/S = (3p - a - b - c)/S = (3p - 2p)/S = p/S = 1/r,

since S = rp.

### ra + rb + rc = r + 4R

As we know,

S = rp,

and also

S = ra(p - a) = rb(p - b) = rc(p - c).

From these we have

 (4) ra + rb + rc - r = S(1/(p - a) + 1/(p - b) + 1/(p - c) - 1/p).

Simple algebra yields

1/(p - a) + 1/(p - b) = c / (p - a)(p - b) and1/(p - c) - 1/p = c / p(p - c).

And a little more effort makes a great payoff:

c / (p - a)(p - b) + c / p(p - c) = abc / p(p - a)(p - b)(p - c) = abc / S²,

by Heron"s formula. Khổng lồ sum up, from (4)

 (5) ra + rb + rc - r = S·abc/S² = abc / S.

However, abc = 4RS, so that (5) implies exactly what"s needed:

ra + rb + rc - r = abc / S = 4R.

### rarbrc = pS

Since

S = ra(p - a) = rb(p - b) = rc(p - c),

we immediatly obtain

 rarbrc = S3 / (p - a)(p - b)(p - c) = S3 / ,

by Heron"s formula. But

S3 / = Sp.

### r+R=R(cos(A)+cos(B)+cos(C))

We know that

r + rc + rb - ra = 4Rcos(A),r + rb + ra - rc = 4Rcos(C),r + ra + rc - rb = 4Rcos(B)

So that 3r+(ra + rb rc=4R(cos(A)+cos(B)+cos(C)). But

ra + rb + rc = r+4R

which combine into 4r+4R=4R(cos(A)+cos(B)+cos(C)), exactly as required.

### rrarbrc = S²

This is an immediate consequence of rarbrc = pS and rp = S.

### la = 4p(p-a)bc/(b+c)²

Follows from la = 2bc cos(A/2)/2 & cos²(A/2) = p(p - a) / bc.

### la = 2bc cos(A/2)/(b+c)

Applying the sine area formula to triangles ABLa and ACLa và then lớn the entire ΔABC we see that

blasin(A/2)/2 + clasin(A/2)/2 = bc sin(A)/2

This simplifies to

la = bc sin(A)/ (b + c)sin(A/2) = 2bc cos(A/2) / (b + c).

### ma² = (b² + c²)/2 - a²/4

Let"s use Stewart"s theorem

AB²·DC + AC²·BD - AD²·BC = BC·DC·BD

with D being the midpoint M of BC. Then AB = c, DC = a/2, AC = b, BD = a/2, AD = ma, BC = a. We have,

c²·a/2 + b²·a/2 - ma²·a = a·a/2·a/2.

(The above identity could be as easily obtained with the help of the Theorem of Cosines or the Parallelogram Law; here is an example.)

### abc = 4RS Let AD be a diameter of the circumcircle of ΔABC & AH its altitude. Right triangles AHC and ABD are similar, for ∠ADB = ∠ACH. Therefore,

In other words,

2R·AH = AB·AC = bc.

And finally

abc = 2R·AH·a = 4RS.

### bc = 2Rha

This follows from the previous derivation or by substituting S = aha/2 into the final formula.

### p = 4Rcos(A/2)·cos(B/2)·cos(C/2)

By the Law of Sines

a = 2R·sinA, b = 2R·sinB, c = 2R·sinC,

so that

 p = R·(sinA + sinB + sinC) = R·(sinA + sinB + sin(180° - A - B) = R·(sinA + sinB + sin(A + B) = R·(sinA + sinB + sinA·cosB + cosA·sinB) = R·(sinA·(1 + cosB) + sinB·(1 + cosA)) = R·(2sin(A/2)cos(A/2)·2cos²(B/2) + 2sin(B/2)cos(B/2)·2cos²(A/2)) = 4R·cos(A/2)cos(B/2)(sin(A/2)cos(B/2) + sin(B/2)cos(A/2)) = 4R·cos(A/2)cos(B/2)sin((A + B)/2) = 4R·cos(A/2)cos(B/2)sin(90° - C/2) = 4R·cos(A/2)cos(B/2)cos(C/2).

### S = 2R²sin(A)·sin(B)·sin(C)

By the Law of Sines

a = 2R·sinA, b = 2R·sinB,

For the area of the triangle we have

 2S = ab·sinC = 2RsinA·2RsinB·sinC = 4R²·sinA·sinB·sinC.

### r = 4Rsin(A/2)·sin(B/2)·sin(C/2)

This follows directly from

S = rp,p = 4Rcos(A/2)·cos(B/2)·cos(C/2), andS = 2R²sin(A)·sin(B)·sin(C).

### cot(A/2) + cot(B/2) + cot(C/2) = cot(A/2)·cot(B/2)·cot(C/2)

This is equivalent to lớn showing that, for A + B + C = 180°,

cos(A/2)sin(B/2)sin(C/2) + sin(A/2)cos(B/2)sin(C/2) + sin(A/2)sin(B/2)cos(C/2)= cos(A/2)cos(B/2)cos(C/2).

Let"s transform the left-hand side:

cos(A/2)sin(B/2)sin(C/2) + sin(A/2)cos(B/2)sin(C/2) + sin(A/2)sin(B/2)cos(C/2)= sin((A+B)/2)sin(C/2) + sin(A/2)sin(B/2)cos(C/2).

But since (A + B)/2 C = 90° - C/2, this equals

cos(C/2)sin(C/2) + sin(A/2)sin(B/2)cos(C/2) = cos(C/2).

Reversing the steps:

 sin(C/2) + sin(A/2)sin(B/2) = cos((A+B)/2) + sin(A/2)sin(B/2) = cos(A/2)cos(B/2) - sin(A/2)sin(B/2) + sin(A/2)sin(B/2) = cos(A/2)cos(B/2).

Combining everything together we get the desired identity.

### rR = abc / 4p

r² = p-1(p - a)(p - b)(p - c) is equivalent to

r = √D / p,

where D = p(p - a)(p - b)(p - c). Also,

R = abc / 4√D.

Multiplying the two gives

rR = abc / 4p.

Note that the identity at hand also follows by combining S = rp with abc = 4RS.

Xem thêm: Hiện Tượng Siêu Dẫn Điện Là Hiện Tượng Siêu Dẫn Là, Sự Phụ Thuộc Của Điện Trở Suất Vào Nhiệt Độ

### AH = 2R·|cos(A)|

In ΔABH, if A b is right.) Applying the law of sines khổng lồ ΔABH gives,

 AH / sin(∠ABH) = AB / sin(180° - ∠C) = AB / sin(∠C) = 2R

from the lawa of sines applied in ΔABC. Thus

 2R = AH / sin(∠ABH) = AH / sin(90° - ∠A) = AH / cos(∠A),

which proves the assertion AH = 2R·|cos(A)| when A

For the case where ∠A is obtuse, H falls outside ΔABC, ∠ABH = ∠A - 90° so at the end we"ll get AH = -2R·cos(A), proving AH = 2R·|cos(A)| in this case also.